Development and validation of the laziness assessment scale - Euckie U. Immanuel; Obinna O. Ike (Social Sciences and Humanities Open, 2025)
Laziness, a behavioural construct with implications in psychological, social, and organizational contexts, has garnered attention owing to its impact on human functioning. Limited research has explored how this construct affects individuals' functioning as the subjective nature of laziness necessitates a reliable measurement tool. This study addresses this gap by developing and validating a Laziness Assessment Scale to measure laziness levels, thus addressing the absence of a standardized tool across diverse populations. A three-stage process was developed and validated using the Laziness Assessment Scale (LAS). Data were collected from 2493 students, workers, and managers from various sectors of Southeast Nigeria. Expert evaluation establishes face and content validity. Exploratory factor analysis (EFA) of 1920 participants and confirmatory factor analysis (CFA) of 336 participants revealed a one-factor, 9-item structure. A study of 237 participants validated the construct validity of the 9-item scale. Factor analysis, Cronbach's alpha, and Pearson's coefficient were used to assess factor structure, reliability, and validity indices. The scale demonstrated strong reliability, with a Cronbach's alpha of .91 and split-half reliability of .86. For concurrent validity, the scale correlated positively with procrastination, Generalized Anxiety Disorder, depression, and external locus of control and negatively with conscientiousness and assertiveness for predictive validity. These findings indicate that the LAS exhibits strong psychometric properties, validating its effectiveness in capturing variations in laziness. This study has implications for individual assessments because understanding laziness levels can inform interventions to enhance productivity across populations owing to the impact of laziness on health behaviours, well-being, and productivity outcomes.